Health behaviors of patients with ischemic heart disease undergoing early cardiac rehabilitation in the age range of 45-60 years - Bąk, Ewelina; Procner, Grażyna (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Along with the development of civilization, civilization diseases appear, which take the form of the highest death rates, mainly in the field of cardiovascular diseases. It is largely related to the accumulation of negative consequences of improper health habits, as well as reduced physical activity. The aim of the study was to present the impact of health behaviors on the example of patients with ischemic heart disease treated with the CABG method, undergoing early cardiac rehabilitation at the "Równica" Health Resort in Ustroń, at the 2nd Cardiac Rehabilitation Department. Materials and methods: The study was conducted among 81 patients, after coronary artery bypass surgery (CABG), rehabilitated at the 2nd Department of Early Cardiac Rehabilitation at the "Równica" Health Resort in Ustroń. The research was conducted from 10.2021 to 02.2022. The Health Behavior Inventory (IZZ) according to Juszczyński and an own questionnaire were used for the research. Research results: According to the data analysis, Proper Eating Habits scored the highest, followed by Preventive Behavior and Positive Mental Attitude, and the lowest - Health Practices. Conclusions: Based on the analysis of the conducted research, it can be concluded that people with ischemic heart disease do not care for their health properly. Women and the elderly, as well as physically active people, fare better in this respect.